Outcomes After Patellofemoral Arthroplasty With the Arthrex iBalance—A Third Generation Implant - Elizabeth C. Bond, MB, ChB, FRACS; Emily K. Reinke, PhD; Christian Zirbes, BS; Emily Poehlein, MB; Cynthia L. Green, PhD; Richard M. Danilkowicz, MD; Annunziato Amendola, MD (Arthroplasty Today, 2025)
Background: Patellofemoral arthroplasty (PFA) is an attractive option for patients who have isolated patellofemoral disease. This study aimed to assess the functional outcomes and revision rates of primary PFA with a third-generation implant with short- to medium-term follow-up. Methods: We retrospectively reviewed the records of 49 patients (70 knees) undergoing PFA with the iBalance system by a single surgeon at a quaternary center between January 2015 and September 2022 for demographic and surgical data, as well as complications and revision rates. Patient-reported outcome scores were then collected. Results: The population was majority female (81.6%) with a median age of 50 years. Four knees were revised to a total knee arthroplasty (5.7%) at an average time point of 2.3 years postoperatively (range: 1.3-3.5 years). The median Single Assessment Numeric Evaluation score at the time of follow-up was 82.5, while the median Kujala score was 72. Lower preoperative Kellgren-Lawrence grade was significantly associated with lower Knee Injury and Osteoarthritis Outcome Scores in all 5 domains (P < .05 for all). Additional procedures were required in 17 knees (24.3%), in most cases to improve patella tracking. Conclusions: This study is, to our knowledge, the first to examine outcomes of the iBalance PFA system. The results show favorable patient-reported outcomes in this cohort consistent with other 2nd and 3rd generation PFA implants, along with a revision rate similar to its prosthetic peers.